2009
DOI: 10.1111/j.1365-3156.2009.02380.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and burden of disease from Japanese encephalitis in Cambodia: results from two years of sentinel surveillance

Abstract: Summaryobjectives To describe the results from two years of Japanese encephalitis (JE) sentinel surveillance in Cambodia. conclusions JE is an important cause of meningoencephalitis in Cambodian children. As JE is a vaccine-preventable disease, an immunization programme could result in a considerable reduction in morbidity and mortality from JE among children in Cambodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Using serological and molecular testing, JEV was the most common cause of AME in this study, with 20.3% of cases ‘confirmed’ or ‘highly probable’ for JEV infection; and a further 4.1% classified as ‘suspected’. These findings support previous studies conducted in Cambodia, 11, 18, 19 and indeed the region, 8, 17, 20, 21, 22 reporting JEV as the main cause of infectious paediatric encephalitis. These findings should provide impetus for initiatives to further roll out JEV vaccination in the region.…”
Section: Discussionsupporting
confidence: 91%
“…Using serological and molecular testing, JEV was the most common cause of AME in this study, with 20.3% of cases ‘confirmed’ or ‘highly probable’ for JEV infection; and a further 4.1% classified as ‘suspected’. These findings support previous studies conducted in Cambodia, 11, 18, 19 and indeed the region, 8, 17, 20, 21, 22 reporting JEV as the main cause of infectious paediatric encephalitis. These findings should provide impetus for initiatives to further roll out JEV vaccination in the region.…”
Section: Discussionsupporting
confidence: 91%
“…• Incidence Group C1: Overall incidence is 3.3 per 100 000 (weighted average of results from Yin et al 20 and Xufang et al 13 ); the child to adult case frequency ratio is 3:1 (based on the ratio of 156 cases in 0-14-year-olds to 57 cases in persons aged > 14 years among combined residents and non-residents, as reported by Yin et al 20 25 Kari et al 26 and Hoke et al 27 ); the child to adult case frequency ratio is 7:1 (based on the ratio of 43 childhood cases to 6 adult cases detected from July 2001 through 2006 by Wong et al 32 ).…”
mentioning
confidence: 80%
“…Each of these papers (or the English translation of five Chinese-language papers) was then carefully reviewed by at least two authors to further cull the list, resulting in a final group of 12 studies that provided original, recent population-based and largely laboratory-confirmed incidence data (or hospital-based incidence data in a defined population). 13,20,[23][24][25][26][27][28][29][30][31][32] These 12 studies consisted of one study each from Bangladesh, Cambodia, Indonesia, Malaysia and Thailand, two from China (excluding Taiwan) two from Japan and three from Nepal. They represented all but three (B, E and I) of the 10 incidence groups (Table 1).…”
Section: Incidence Datamentioning
confidence: 99%
“…Cambodia is a JE high-incidence country with a nascent vaccination programme that should develop into a national program in the coming years [4]. A sentinel surveillance study on Japanese encephalitis in six Cambodian hospitals estimated the clinically-declared JE incidence in 2007 in the country at 11.1 cases per 100 000 children under 15 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…A sentinel surveillance study on Japanese encephalitis in six Cambodian hospitals estimated the clinically-declared JE incidence in 2007 in the country at 11.1 cases per 100 000 children under 15 years of age [4]. …”
Section: Introductionmentioning
confidence: 99%